LIMITATION FOR THE PRACTICE OF EXCESSIVE RELIGIOUS MODERATION (International Conference on Social and Islamic Studies, 2022)
Religious moderation is urgent to be implemented in Indonesia because Indonesia is a diverse country in united. However, the fact is that there are practices of excessive religious moderation that tend to be extreme. So that in order to restore the meaning of religious moderation that Wasathiyyah is in the middle as mandated by Allah SWT. in the Qur'an Surah Al-Baqarah verse 143, it is necessary to limit the practice of religious moderation. So we need a concrete solution to this problem. So this research has several objectives, namely to: (1) Describe excessive religious moderation practices, (2) Analyze efforts to limit excessive religious moderation practices. As for this research is a type of qualitative research. So the research method used is a normative approach that collects data by means of literature studies from some of the literature used. The results and discussion of this study is that the excessive practice of religious moderation is the intention of carrying out religious practices with the aim of moderation not being strict but too loose so that it tends to give rise to a new pole of liberal extremism that leads to polytheism. For example, General "D"'s controversial statement and Gus Samsudin's medical practices. The efforts to limit the practice of excessive religious moderation are carried out by studying and understanding the 4 (four) indicators or limitations of religious moderation by the Ministry of Religion of the Republic of Indonesia, namely a strong national commitment, being tolerant properly, being non-violent, and accommodating to local culture. So that the practice of religious moderation can be carried out properly and not excessively which tends to be extreme.